Relationship between Driver’s Dynamic Pressure Distribution with their Anthropometric Variables on Car Seat under Paved Road - Mat Tahir, Mohd Faizal; Khamis, Nor Kamaliana; Wahab, Dzuraidah; Sabri, Nabilah; Hasani, Zulaikha (International Journal of Integrated Engineering, 2020)
Driving is a task that requires physical and emotional demands of the driver to control the car while sitting. The driver’s condition may be affect due to this repetitive driving task, which can be determined through the performance of alertness, signs of discomfort as well as fatigue level experience by the driver. Past studies showed that anthropometric variable is one of the factor in determining human’s performance while performing an activity. However, there is still a lack of systematic explanation on how it relates to driving activity under different road conditions. Thus, this research objectives to determine the relationship between selected driver’s anthropometric variables with dynamic pressure distribution experienced on the car seat while driving on paved road under normal driving task. A total of 44 subjects participated in this study. Tactilus pressure sensor was used to record the pattern of pressure distribution while driving. Based on the finding, there is a mild correlation with r =0.61 and (R2 = 0.38) between dynamic pressure on the right thigh with height and weight of the subject. The study revealed that nearly 40 percent of the variance in the dynamic pressure on the left thigh is predictable from the height and weight of the subject.